LGR5 is a negative regulator of tumourigenicity, antagonizes Wnt signalling and regulates cell adhesion in colorectal cancer cell lines. - Francesca Walker (Public Library of Science (PLoS), 2011)
Background LGR5 (Leucine-rich repeat-containing G-protein coupled receptor 5) is the most established marker for intestinal stem cells. Mouse models show that LGR5+ cells are the cells of origin of intestinal cancer, and LGR5 expression is elevated in human colorectal cancers, however very little is known about LGR5 function or its contribution to the stem cell phenotype and to colorectal cancer. Principal findings We have modulated the expression of LGR5 by RNAi (inhibitory RNAs) or overexpression in colorectal cancer cell lines. Paradoxically, ablation of LGR5 induces increased invasion and anchorage-independent growth, and enhances tumourigenicity in xenografts experiments. Conversely, overexpression of LGR5 augments cell adhesion, reduces clonogenicity and attenuates tumourigenicity. Expression profiling revealed enhanced wnt signalling and upregulation of EMT genes upon knockdown of LGR5, with opposite changes in LGR5 overexpressing cells. These findings suggest that LGR5 is important in restricting stem cells to their niche, and that loss of LGR5 concomitant with activated wnt signalling may contribute to the invasive phenotype of colorectal carcinomas.